Neuroendocrine Liver Metastasis: Prognostic Implications of Primary Tumor Site on Patients Undergoing Curative Intent Liver Surgery - Spolverato, G (2018)
BACKGROUND: Neuroendocrine tumors typically arise from pancreatic (PNET) vs. gastrointestinal or thoracic origins (non-PNET). The impact of primary tumor site on long-term prognosis following resection of neuroendocrine liver metastasis (NELM) remains poorly defined. The objective of the current study was to define the association of primary tumor location on prognosis of patients undergoing curative intent liver resection for NELM. METHODS: Between 1990 and 2014, 421 patients who underwent resection of NELM were identified from a multi-institutional database. Clinicopathological characteristics, operative details, and outcomes were stratified and analyzed by location of the primary tumor (PNET vs. non-PNET). A propensity score-matched analysis was utilized to assess the impact of primary tumor location on long-term survival. RESULTS: Among the 421 patients, 197 (46.8%) patients had NELM from a PNET primary while 224 (53.2%) had a non-PNET primary (small bowel, n = 145; rectal, n = 10; bronchial, n = 22; other, n = 47). There were no differences in tumor burden and tumor site, while presence of extrahepatic disease was more common among patients with non-PNET NELM (extrahepatic disease, PNET NELM, n = 11 27.5% vs. non-PNET NELM, n = 29 72.5%; p = 0.010). Patients with PNET NELM were more likely to have non-functional disease compared with patients who had non-PNET NELM (non-functional, PNET NELM, n = 117 54.9% vs. non-PNET NELM, n = 96 45.1%; p = 0.011). On the final pathological specimen of the resected NELM, patients with PNET NELM were more likely to have a moderately differentiated tumor (59.3%), while patients with non-PNET NELM were more likely to have a poorly differentiated tumor (67.8%) (p = 0.005). Patients with PNET NELM had a worse 5-year DFS and 5-year OS compared with patients who had non-PNET NELM (DFS, PNET 36.2% vs. non-PNET 55.2%; p = 0.001 and OS, PNET 79.5% vs. non-PNET 83.4%; p = 0.008). After propensity score matching, both 5-year DFS and 5-year OS of the PNET and non-PNET groups were comparable (DFS, PNET 46.2% vs. non-PNET 55.9%; p = 0.22 and OS, PNET 81.5% vs. non-PNET 84.3%; p = 0.19). CONCLUSION: PNET patients more often present with non-functional NELM and moderately differentiated tumors. On propensity-matched analysis, factors such as extrahepatic disease and tumor grade, but not primary tumor location, were associated with prognosis of patients undergoing curative intent liver surgery for NELM.